Exponential Mean Modeling of Coping Strategies and Dietary Diversity During the COVID-19 Pandemic in Mozambique - Abayomi Samuel Oyekale (Research Synergy Foundation, 2024)
The COVID-19 pandemic has brought significant socioeconomic problems to many developing countries. In Mozambique, the impacts of the pandemic were felt in different spheres of households’ livelihoods. This study contributes to the existing body of knowledge by analyzing the effects of coping strategies and other factors on households’ dietary diversity scores (HDDS). The data were collected in two non-longitudinal waves in 2021 and 2022 from 3975 households by the Food and Agriculture Organization (FAO). The instrumental Poisson regression model was used for data analysis. The results showed that across the two periods, cereals were mostly consumed (96.93%), while meats (15.75%), milk and dairy (13.99%), and eggs (9.16%) were the least consumed. There was an increment in the proportion of households that consumed between zero and four food groups. Furthermore, there were declines in the utilization of coping strategies, while depletion of savings (50.62%) and credit (45.21%) were mostly used. The instrumental variable Poisson regression results revealed that expected HDDS decreased significantly (p<0.05) with sold animals, eating elsewhere, consumption of seed stock, decreased agricultural input expenditures, and emergency begging, whereas illegal activities increased it. In addition, household incomes, crop farming, and being younger than 35 years significantly increased (p<0.05) the expected HDDS, while all regions except Gaza had significantly higher expected HDDS than Cabo Delgado. It was concluded that adopted coping mechanisms could not offset households’ food problems during the pandemic, although some regional differences existed. Therefore, initiatives to promote human nutrition in Mozambique should enhance households’ resilience to income shocks through region-specific income-promoting activities.